Scattering of Atomic Hydrogen Off a H-Covered W(110) Surface: Hot-Atom versus Eley-Rideal Abstraction Dynamics - Pétuya, R. (2015)
Normal incidence scattering of hydrogen atoms off a H-covered tungsten W(110) surface is simulated via quasiclassical trajectories. A density functional theory (DFT) based multiadsorbate potential is developed to model a wide range of surface coverages, θ = 0.25–1 monolayer (ML), reproducing the surface arrangements observed at low temperature. The competition between hot-atom (HA) and Eley–Rideal (ER) abstraction mechanisms is studied for collision energies of the projectile atom in the range Ep = 0.1–5.0 eV (Ep = 0.1–2.0 eV) for θ = 0.25 ML (θ = 0.5, 0.75, and 1 ML) coverage. Cross sections, final energies of the recombination products, and reaction times are analyzed. At low coverage and low collision energy, HA dominates the abstraction, whereas HA and ER cross-sections become similar when collision energy increases. The vibrational distribution of recombined H2 molecules at finite coverage is found to be in better agreement with experiments than the one computed within the single adsorbate limit. At high surface coverage, ER dominates abstraction but the dynamical observables highlight the similarity between both reaction mechanisms, thus suggesting that abstraction may be considered as a unique process.